2018
DOI: 10.1038/s41598-018-20021-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and accumulation of dietary ergothioneine and its metabolites in mouse tissues

Abstract: L-ergothioneine (ET) is a diet-derived amino acid that accumulates at high concentrations in animals and humans. Numerous studies have highlighted its antioxidant abilities in vitro, and possible cytoprotective capabilities in vivo. We investigated the uptake and distribution of ET in various organs by a highly sensitive and specific liquid chromatography coupled tandem mass spectrometry (LC-MS/MS) technique, both before and after oral administration of pure ET (35 and 70 mg/kg/day for 1, 7, and 28 days) to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 63 publications
11
129
0
1
Order By: Relevance
“…Multiple modes of action by ET suggest that this unique dietary compound may be able to target various pathological aspects of AD. First and foremost, ET can cross the BBB, with several reports of ET in animal and human brains, and expression of the ET transporter, OCTN1 in rodent brains (cerebellum, hippocampus, and cortex) . We have also identified the presence of ET in post‐mortem human brain and cerebrospinal fluid (unpublished data).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Multiple modes of action by ET suggest that this unique dietary compound may be able to target various pathological aspects of AD. First and foremost, ET can cross the BBB, with several reports of ET in animal and human brains, and expression of the ET transporter, OCTN1 in rodent brains (cerebellum, hippocampus, and cortex) . We have also identified the presence of ET in post‐mortem human brain and cerebrospinal fluid (unpublished data).…”
Section: Discussionsupporting
confidence: 55%
“…This extension in mean and maximal lifespan with ET treatment would equate to years when translated to a human lifespan, but more importantly, the increased healthspan would lead to a significant reduction in morbidity and societal burden. It should also be noted that numerous animal and human studies have demonstrated that blood and tissue levels of ET are capable of reaching millimolar levels hence validating the feasibility of the doses tested in the nematodes .…”
Section: Discussionmentioning
confidence: 84%
“…This could happen by multiple mechanisms of course, such as changes in diet and/or OCTN1 transporter activity. Dietary ET does cross the blood–brain barrier, since it can be measured in human cerebrospinal fluid and postmortem brain samples (our unpublished data; also see ) and readily enters the brain when administered to mice . A Japanese study has found a correlation between increased intake of mushrooms (one of the most important dietary sources of ET ; Table ) and lower incidence of dementia.…”
Section: Ergothioneine As a Potential Treatment For Diseasesmentioning
confidence: 82%
“…Ergothioneine can accumulate to high levels in some human and animal tissues, including red blood cells (with basal levels of ~ 125 μ m and ~ 220 μ m in human and mouse whole blood, respectively, and millimolar levels reported in red blood cells ), liver and spleen (with basal levels of ~ 350 μmol·g −1 tissue and ~ 100 μmol·g −1 tissue in mouse liver and spleen, respectively) . Our recent study demonstrated that when ET is orally administered to mice, it accumulates rapidly in the liver and blood cells but also enters most (or perhaps all) other tissues, including brain, heart, lung, kidney, spleen and eye. Since animal sera are commonly used in cell culture media, ET is even present in cell cultures.…”
Section: Ergothioneine In Tissues Extracellular Fluids and Cell Culturementioning
confidence: 97%
See 1 more Smart Citation